Sobre corpos que “não podem” aparecer : memórias de escola nas narrativas de pessoas travestis - Alexandre, Bruno do Prado (2017)
To promote debates and discussions led to problematize the right to difference and the respect for diversity in a world in search of homogenization and universalization of parameters and values. It is an urgent and necessary issue reflects on. In these terms, think about school is make evidence which it has often been a place of (re)production of inequalities adjusted intensely in sexist, homophobic, masculine, racist and essentialist discourses dealing with human sexuality only through dualist perspective between masculine and feminine. In this backdrop is relevant to think about certain important points that have crossed school, such as gender and sexuality issues. These ones wonder how bodies are been perceived in that place and what practices based on these perceptions are been built day after day through the maintenance and legitimization of rules which has aimed to define control and to discipline bodies and or through respect to subjective differences that in search of problematize these rules. The current research is bounded to Programa de Pós-Graduação em Educação (PPGEdu/CUR/UFMT) na linha de pesquisa “Linguagens, Cultura e Construção do Conhecimento: Perspectiva histórica e contemporânea” e pertencente ao grupo de pesquisa “Infância, Juventude e Cultura Contemporânea” (GEIJC). The main purpose of this study is to understand from Transvestites’ memories, how they have attributed meanings and new meanings to their experiences felt and lived inside school. These experiences refer to body, gender and sexuality issues, in temporal and spatial aspects of school. It is as a way to problematize, in the current days, some institutional discourses of this place and to check other senses to subjective changes experienced in Travesties bodies. The authors and theoretical references are about gender and post/feminist studies. The research in question is from qualitative approach and it had as methodological strategy some interviews with five Transvestites. They were recorded in digital voice recorder and registered in fieldwork notebook. This study was conducted by a queer perspective; it is anchored in dialogism and otherness Mikhail Bakthin’s concepts as well. Therefore these analyses focus on narratives experienced by Transvestites in the school. They bring institutional discourses on their infant bodies as well as different segregation and normalization mechanisms who they were submitted by Education Physical classes, by school daily activities or still when they have used toilets. In a deep analyze the school presents itself like a social space full tensions and contradictions, therefore it is crossed by discourses which bring imprisoned morality, on the other hand, there are some people are crying against this gag. These voices need echo in the school and inside of the curricula as well.